Removal of Fluorine from the Waste Acid of Lead Smelter - Li, Jiayuan; Yang, Tianzu; Zhou, Zhaoan (Asian Journal of Chemistry, 2012)
Based on thermodynamic data, using lead ions to remove the fluoride in the waste acid solution was studied. Lead-fluoride ion-water system E-log [F–] diagram and the solubility curve of lead fluoride was drawn at 25 ºC. When lead oxide or the other materials such as the lead blast furnace dust and lead ash were used as the precipitant, the removal rate of fluoride is more than 90 % under proper conditions in the waste acid solution.